The Role of Green Human Resources Management in Supporting the Implementation of the ISO 14001 Environmental Management System at Inspection Companies in Indonesia - Sherly Sherly; Lenny C. Nawangsari (Inclusive Society and Sustainability Studies, 2022)
Environmental awareness for the sake of ecosystem sustainability is proven to have a positive influence on the development of various forms of management in various fields. In operations management, an environmental management system standard has even emerged, which helps organizations to manage their business activities while taking into account the aspects and their impact on the environment, known as ISO 14001. For Human Resource Management (HRM), Green Human Resource Management (GHRM) is currently being widely implemented. The study then discusses in more detail how inspection companies in Indonesia, especially in the oil and gas sector, implement GHRM. The study also examines its relation to implementing the ISO 14001 environmental management system as compliance with regulations set by the Government, bearing in mind that the ISO 14001 standard contains requirements regarding HRM and the contribution of these human resources in organizational policies in the field of environmental preservation. Using qualitative research methods and data analysis processes using NVivo 12, the final results of this study found a link between GHRM and ISO 14001, and these interactions are related to one another. Furthermore, this study also looks further at the ideal model concept that can be applied as an illustration of the integration of GHRM and ISO 14001.